1997
DOI: 10.1016/s0032-3861(96)00756-2
|View full text |Cite
|
Sign up to set email alerts
|

Stereocomplexation of sPMMA-PBD-sPMMA triblock copolymers with isotactic PMMA: 1. Thermal and mechanical properties of stereocomplexes

Abstract: A novel thermoplastic elastomer consisting of a triblock copolymer (MBM) with outer syndiotactic poly(methyl methacrylate) (sPMMA) blocks associated to an inner polybutadiene (PBD) block has been modified by stereocomplexation with isotactic PMMA (iPMMA). Solution cast films of stereocomplexes have been analysed by thermal analysis as a function of the iPMMA/sPMMA (i/s) mixing ratio and the solvent used for the film casting. Although self-aggregation of iPMMA is currently observed, this phenomenon does not occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
3
9
0
Order By: Relevance
“…The first T g value corresponds to the PS block (101 ºC), and the second to the PMMA block (122 ºC). The T g (122 ºC) was similar to the value determined by Yu et al 23 for syndiotactic PMMA (125 ºC), suggesting that the PMMA tacticity (in the copolymer) was not the same as that observed for PMMA when pure or as a component in the blend. The side chain of isotactic PMMA is characterized by high frequency in the rotation (high mobility) which is associated with a T g lower than the syndiotactic value.…”
Section: Characterization Of the Filmssupporting
confidence: 77%
“…The first T g value corresponds to the PS block (101 ºC), and the second to the PMMA block (122 ºC). The T g (122 ºC) was similar to the value determined by Yu et al 23 for syndiotactic PMMA (125 ºC), suggesting that the PMMA tacticity (in the copolymer) was not the same as that observed for PMMA when pure or as a component in the blend. The side chain of isotactic PMMA is characterized by high frequency in the rotation (high mobility) which is associated with a T g lower than the syndiotactic value.…”
Section: Characterization Of the Filmssupporting
confidence: 77%
“…PMMA stereocomplexes were formed within multi-block TPEs leading to a significant improvement of thermal properties relative to noncomplexed analogues (Figure 2). [330][331][332][333][334][335][336] In such systems the stereocomplexed PMMA segments were implicated as physical cross-links. The in situ stereocomplexing polymerization of methyl methacrylate furnished sc-PMMA that was highly crystalline, but surprisingly optically transparent as well.…”
Section: Pmmamentioning
confidence: 99%
“…Stereocomplexes of i-PMMA or s-PMMA with diblock-or triblockcopolymer have been reported, such as polyisobutylene block copolymers (67,68), poly(dimethylsi1oxane) block copolymers (69), and polybutadiene (PB) block copolymers (70,71). Yu and Jerome have reported that stereocomplexation of tactic polymers increases the tensile strength of PMMA-PB-PMMA copolymers, containing small s-PMMA blocks at constant molecular weight of PB and i-PMMA, whereas an opposite effect is observed for longer s-PMMA blocks (71).…”
Section: Complex Formation In Mixtures Of Pmma Of Opposite Tacticitiesmentioning
confidence: 99%